lslamic view on reconstructive surgery: a child with polydactily as a case study - Sharifudin, Mohd Ariff; Che Ahmad, Aminudin; Abdul Rahman, Ahmad Fadhil; Jeffery, Mardhiah; Zabidi, Siti Nur Azreena; Ibrahim, Ahmad Syahid; Mohamad Sha, Shazwan; Mohd Rafee, Adilah Rafi'ah; Zainun, Norsafina (2013)
Islamic Input in Orthopaedics (Triple IO) was designed to infuse Islamic perspectives into the contemporary orthopaedic undergraduate curriculum. The one day program is divided into case discussions and practical sessions. One of the cases discussed was a child with polydactily. The case was presented in the form of Problem Based Question (PBQ), as students are familiar with this format during their pre-clinical years. The session was facilitated by orthopaedic surgeons and a fiqh scholar from the Kulliyyah of Islamic Revealed Knowledge, IIUM. The learning processes involved were literature search, identification of problems and their solutions, group presentation, and interactive discussions. Discussions included approach of the case from orthopaedic surgeons' perspective as well as related Islamic rulings. The feedback given by the students at the end of the program was overwhelming positive. They would like more of such session to be scheduled.